Market Power in the Retail Food Industry: Evidence from Vermont - Cotterill, Ronald W. (The Review of Economics and Statistics, 1986)
Abstrac-t-The profits of leading firms in concentrated markets may be due to market share related cost efficiencies or market power. One way to identify the separate effect of market power is to analyze the relationship of market concentration and market share to the prices charged by firms in local geographic markets. This study analyzes the prices charged by supermarkets in local Vermont markets. Prices are significantly higher in more concentrated markets. The Herfindahl index, as a concentration measure, out-performs the four-firm or one-firm concentration ratio. Herfindahl marginally out-performs a firm's market share as a predictor of its price level.